A Rare Case Report on Distal Spinal Muscular Atrophy (SMA) - Rahaman, Habibur; Islam, Md Rafiqul; Hannan, MA; Jannat, Maftahul (Bangladesh Journal of Neuroscience, 2016)
Spinal muscular atrophies (SMA) are heterogeneous group of motor system disorders of alpha motor neuron clinically characterized by progressive lower motor neuron features. The distal form of SMA is an extremely rare disorder, which usually presents in the young adults and has a relatively slow progression with almost normal life-span. Differential diagnosis of this syndrome includes hereditary motor sensory neuropathy- Charcot-Marie-Tooth disease (CMT) and distal myopathies, which should be excluded before confirming this rare entity. As distal form of SMA is a very extremely rare condition so we would like to present a young male with this disorder and a short discussion of the theoretical aspects. Bangladesh Journal of Neuroscience 2016; Vol. 32 (2): 106-110